Distribution Profile of Inositol 1, 4, 5-Trisphosphate Receptor/Ca2+ Channels in α and β Cells of Pancreas. Issue 1 (January 2015) - Hur, Yong Suk; Yoo, Seung Hyun
<x xml:space="preserve">Abstract</x> Objectives The α and β cells of pancreatic islet release important hormones in response to intracellular Ca2+ increases that result from Ca2+ releases through the inositol 1, 4, 5-trisphoshate receptor (IP3R)/Ca2+ channels. Yet no systematic studies on distribution of IP3R/Ca2+ channels have been done, prompting us to investigate the distribution of all 3 IP3R isoforms. Methods Immunogold electron microscopy was performed to determine the presence and the relative concentrations of all 3 IP3R isoforms in 2 major organelles secretory granules (SGs) and the endoplasmic reticulum of α and β cells of rat pancreas. Results All 3 IP3R isoforms were present in SG membranes of both cells, and the IP3R concentrations in SGs were ∼2-fold higher than those in the endoplasmic reticulum. Moreover, large halos shown in the electron microscope images of insulin-containing SGs of β cells were gap spaces that resulted from separation of granule membranes from the surrounding cytoplasm. Conclusions These results strongly suggest the important roles of SGs in IP3-induced, Ca2+-dependent regulatory secretory pathway in pancreas. Moreover, the accurate location of SG membranes of β cells was further confirmed by the location of another integral membrane protein synaptotagmin V and of membrane phospholipid PI(4, 5)P2.